APPEARANCE OF WATER MICROPOLLUTANTS IN WATER AS EFFECTS OF EXTREME METEOROLOGICAL EVENTS - MOLDOVAN, Zaharie; FEHER, Ioana; MARINCAS, Olivian (Studia Universitatis Babeș-Bolyai Ambientum, 2017)
The objective of the present study is to obtain data on micropollutants sources present in surface and drinking water after extreme meteorological events in Romanian regions. The analyses were performed on water samples collected from potable water sources using GC/MS method after LL extraction. Were detected and discussed anthropogenic compounds from following compound groups: lubricant and plastic additives and hydrocarbons. The compound identification was done based on mass spectra obtained by electron impact ionisation in full scan mode.